Encapsulation of purple corn and blueberry extracts in alginate-pectin hydrogel particles: Impact of processing and storage parameters on encapsulation efficiency. (May 2018) - Guo, Jingxin; Giusti, M. Monica; Kaletunç, Gönül
Abstract: Purple corn (PC) and blueberry (BB) extracts were encapsulated in alginate-pectin hydrogel particles to protect anthocyanins (ACNs) from degradation. Combinations of alginate to pectin ratios at 82 to 18% and 43 to 57% and total gum concentrations (TGC) at 2.2% and 2.8% TGC were prepared to encapsulate both PC and BB ACN. The alginate-pectin hydrogel particles containing PC or BB extracts were produced by dripping solution into pH 1.2 buffer. Blueberry extract encapsulation efficiency was significantly higher than that of purple corn extract due to ACN chemical structure differences and the compatibility between the ACN structures and alginate-pectin hydrogel structure at the low pH environment. Effect of initial ACN concentration in droplets, particle shape, alginate to pectin ratio, TGC, ACN source, and curing bath conditions on encapsulation efficiency after curing (EEm ) was investigated. The initial ACN concentration and particle shape didn't influence the EEm, while the alginate to pectin ratio, TGC, ACN source and the pH of the curing bath showed significant effect on the EEm . The EEm was improved from 26% to 65% for PC ACN and from 48% to 116% for BB ACN by augmenting curing bath with ACN at various concentrations. The ACN retention during storage (ARs ) in hydrogel particles stored in pH 3.0 buffer was improved at low temperature and high particle weight to solution volume ratio. Higher amount of ACN was retained in the hydrogel particles when spherical particles were used. Encapsulation in hydrogel particles significantly reduced the anthocyanin photodegradation upon exposure to fluorescence light. The degradation of ACN was described with a first-order kinetics with half-life values of 630 h for encapsulated PC ACN and 58 h for PC ACN aqueous solution. Hydrogel production and subsequent storage conditions can be optimized to increase the anthocyanin delivered to human body using the low pH beverages such as fruit juices as a delivery vehicle. Graphical abstract: Highlights: Encapsulation efficiency for blueberry was higher than that of purple corn. Encapsulation efficiency improved by increasing alginate and total gum concentration. Anthocyanin loss from hydrogel was minimized at low temperature and solution volume. Encapsulation significantly reduced light-induced ACN degradation rate by up to 10×.